Reward and Punishment Systems on Students' Learning Motivation: An Experimental Study in Semester IV of PPKN Study Program, FKIP Uncen - Lintong, Fikstif Donal (Universitas Trunojoyo Madura, 2024)
This study aiming test impact system reward and punishment to motivation Study 4th semester students of the PPKn Study Program, FKIP, Cenderawasih University through design experiment quasi pretest- posttest control group . Participants consists of of 40 students who were divided become group experiment ( receive) intervention reward and punishment ) and control ( learning) conventional ). The data collected and then analyzed , as well as observation participation , and reflection students . Quantitative results show improvement significant motivation Study group experiment ( mean pretest score : 3.1; posttest : 4.2), while group control No experience change meaningful . Analysis qualitative revealed 75% of students motivated by rewards ( points) add ), but 30% felt worried to punishment . Findings key highlight importance adaptation system incentive with culture Papuan collectivism , where 25% of students recommend reward based on group . Research This conclude that system reward and punishment effective increase motivation Study If designed in accordance context cultural , with recommendation practical in the form of integration non-material rewards , punishments reflective , and utilization digital technology . Implications study support Independent Learning Independent Campus (MBKM) policy in create learning student - centered responsive to need local Papua.